Living in Two Worlds: A study of Sudanese Youth living in Melbourne, Australia - Pittaway, Troy (Curtin University, 2022)
This study explored how young males and females aged between 14-21 years, from the South Sudanese community living in Melbourne perceived various issues impacting their daily lives. This included the community perception of being part of gangs and the racial vilification associated with that narrative, familial breakdown and intergenerational conflict, their perceptions of alcohol and drug use, and the positive role sport played in their lives. The study was underpinned by the psychosocial conceptual framework.